1989
DOI: 10.1111/j.1365-2621.1989.tb05959.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Packaging Conditions on the Flavor Stability of Dry Whole Milk

Abstract: The flavor stability of dry whole milk packed with air, nitrogen, or a mixture of 92% nitrogen and 8% hydrogen (NH) in gas-impermeable pouches containing palladium as a catalyst was evaluated by measuring headspace volatile, oxygen, carbon dioxide contents using gas chromatography, brown color formation by reflective spectroscopy, and sensory scores. The headspace volatile and carbon dioxide contents of the dry whole milks packed with air or nitrogen were significantly higher (P ~0.05) than the samples packed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The differences found in oxidation rates between these studies could be due to differences in water activity of the powder, but also to differences in initial oxidative status of the product. Relationships between sensory changes and production of volatile oxidation products have been reported by numerous researchers (19,21,22) and a good correlation between hexanal production and sensory changes has been obtained (21,(23)(24)(25)(26)(27). In two previous studies, we investigated the effect of oxygen levels down to 0.3 mL/L oxygen in the headspace on the rate of lipid oxidation in cream powder (14,15).…”
Section: Introductionmentioning
confidence: 78%
“…The differences found in oxidation rates between these studies could be due to differences in water activity of the powder, but also to differences in initial oxidative status of the product. Relationships between sensory changes and production of volatile oxidation products have been reported by numerous researchers (19,21,22) and a good correlation between hexanal production and sensory changes has been obtained (21,(23)(24)(25)(26)(27). In two previous studies, we investigated the effect of oxygen levels down to 0.3 mL/L oxygen in the headspace on the rate of lipid oxidation in cream powder (14,15).…”
Section: Introductionmentioning
confidence: 78%
“…Min et al (24) found that the production of carbon dioxide and brown colour were oxygen dependent for milk powder stored at 65°C. In an earlier study, Min and Lee, (26) correlated the CO 2 production to formation of Strecker aldehydes.…”
Section: Discussionmentioning
confidence: 99%
“…levels where the oxidation rate would be expected to be proportional to the oxygen partial pressure. Studies on milk powder show a relationship between the oxygen partial pressure and quality loss of the product (2,(11)(12)(13)(14)(15)(16)(17). Tamsma et al (2) found that there was no significant difference in the flavour score between the initial powder and powder packed with an initial concentration of 1 mL/L oxygen in the headspace after 6 months of storage, while Zimmermann et al (12) found that milk powder packed with an initial oxygen concentration of 1 mL/L oxygen in the headspace showed no flavour changes during 12 months of storage.…”
Section: Introductionmentioning
confidence: 99%